2023
DOI: 10.1002/mc.23548
|View full text |Cite
|
Sign up to set email alerts
|

m7G‐related genes—NCBP2 and EIF4E3 determine immune contexture in head and neck squamous cell carcinoma by regulating CCL4/CCL5 expression

Abstract: Aberrant N 7 -methylguanosine (m7G) levels closely correlate with tumor genesis and progression. NCBP2 and EIF4E3 are two important m7G-related cap-binding genes.This study aimed to identify the relationship between the EIF4E3/NCBP2 function and immunological characteristics of head and neck squamous cell carcinoma (HNSCC). Hierarchical clustering was employed in classifying HNSCC patients into two groups based on the expressions of NCBP2 and EIF4E3. The differentially expressed genes were identified between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The efficacy of immunotherapeutic strategy relies heavily on the initial response of immune system and the presence of preexisting immunity. In the context of antitumor response, the essential contributions of CD8+ T cells and NK cells have been widely acknowledged [33] . It is important to investigate the relationship between CAFs and the infiltration of immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of immunotherapeutic strategy relies heavily on the initial response of immune system and the presence of preexisting immunity. In the context of antitumor response, the essential contributions of CD8+ T cells and NK cells have been widely acknowledged [33] . It is important to investigate the relationship between CAFs and the infiltration of immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…According to one research, EIF4E3 depends on cap‐binding activity to operate as a tumour suppressor and compete with EIF4E's growth‐promoting capabilities. In fact, tumours that have increased EIF4E and low EIF4E3 expression demonstrate that EIF4E3 is of essential inhibitory mechanism that is lost in certain cancers 30 . Other investigations have shown that EIF4E3 may prevent oncogenic transformation 31–33 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, NCBP2 and EIF4E3 can influence the immune environment and response to immunotherapy, thereby inducing tumour transformation in patients with HNSCC. 130 Another study showed that clinical adrenocortical carcinoma (ACC) patients with high METTL1 expression had lower levels of CD8+ T‐cell infiltration and higher levels of macrophage infiltration compared with those with low expression, suggesting that METTL1 exerts a profound effect on tumour immunity in ACC 131 (Figure 3 ).…”
Section: The Emerging Roles Of Rna Methylation As Critical Regulators...mentioning
confidence: 99%